Characterization of a Human Respiratory Mucosa Model to Study Odorant Metabolism - Mérignac-Lacombe, Jeanne; Kornbausch, Nicole; Sivarajan, Rinu; Boichot, Valentin; Berg, Kevin; Oberwinkler, Heike; Saliba, Antoine Emmanuel; Loos, Helene; Ehret Kasemo, Totta; Scherzad, Agmal; Bodem, Jochen; Büttner, Andrea; et al. (Journal of agricultural and food chemistry, 2024)
Nasal xenobiotic metabolizing enzymes (XMEs) are important for the sense of smell because they influence odorant availability and quality. Since the major part of the human nasal cavity is lined by a respiratory mucosa, we hypothesized that this tissue contributed to nasal odorant metabolism through XME activity. Thus, we built human respiratory tissue models and characterized the XME profiles using single-cell RNA sequencing. We focused on the XMEs dicarbonyl and l-xylulose reductase, aldehyde dehydrogenase (ALDH) 1A1, and ALDH3A1, which play a role in food odorant metabolism. We demonstrated protein abundance and localization in the tissue models and showed the metabolic activity of the corresponding enzyme families by exposing the models to the odorants 3,4-hexandione and benzaldehyde. Using gas chromatography coupled with mass spectrometry, we observed, for example, a significantly higher formation of the corresponding metabolites 4-hydroxy-3-hexanone (39.03 ± 1.5%, p = 0.0022), benzyl alcohol (10.05 ± 0.88%, p = 0.0008), and benzoic acid (8.49 ± 0.57%, p = 0.0004) in odorant-treated tissue models compared to untreated controls (0 ± 0, 0.12 ± 0.12, and 0.18 ± 0.18%, respectively). This is the first study that reveals the XME profile of tissue-engineered human respiratory mucosa models and demonstrates their suitability to study nasal odorant metabolism.
CRIS-Team Scopus Importer:2024-05-31
Keywords: human respiratory tissue models; nasal odorant metabolism; perireceptor events; tissue engineering; xenobiotic metabolizing enzymes